2014
DOI: 10.5152/tjbh.2014.1940
|View full text |Cite
|
Sign up to set email alerts
|

Carcinosarcoma of the Breast: Case Report

Abstract: Carcinosarcoma of the breast represents less than 1% of primary breast mailgnancies. Both malign epithelial and malign mesenchymal elements exist together in the breast. A 59 year old postmenopausal women presents with a bloody nipple discharge and mass in breast. In left breast 2x1 cm mss detected and excisied. At pathological examination breast carcinosarcoma was detec-ted. Then modified radical mastectomy was performed. Tumor measured 4x4x3.5 cm. Tumor cells were negative for estrogen, progesteron. C-erb-B2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…In den meisten Fällen zeigt sich keine Expression von Östrogen-und Progesteronrezeptoren und/oder HER2neu mit einem sogenannten "Triple-Negativ"-Muster [4]. Der typische klinische Befund ist ein schnell wachsender, tastbarer Tumor [5]. Die 5-Jahres-Überlebensrate für das Karzinosarkom wird in der Literatur mit unter 50 % angegeben und ist damit geringer als bei anderen Subtypen des metaplastischen Karzinoms [6].…”
Section: Introductionunclassified
“…In den meisten Fällen zeigt sich keine Expression von Östrogen-und Progesteronrezeptoren und/oder HER2neu mit einem sogenannten "Triple-Negativ"-Muster [4]. Der typische klinische Befund ist ein schnell wachsender, tastbarer Tumor [5]. Die 5-Jahres-Überlebensrate für das Karzinosarkom wird in der Literatur mit unter 50 % angegeben und ist damit geringer als bei anderen Subtypen des metaplastischen Karzinoms [6].…”
Section: Introductionunclassified
“…The clinical symptoms of breast carcinosarcoma are similar to invasive ductal carcinoma, and include the presence of a large painful mass, nipple discharge, nipple depression, and skin ulceration (7,8,12,14). One study reported a case of carcinosarcoma presenting as a breast abscess (15).…”
mentioning
confidence: 99%
“…Chemotherapy may include CMF (cyclophosphamide, methotrexate, and 5 fluorouracil)-based TA (anthracyclines/taxane) regimes, but side effects are undesirable (16). Radiation therapy is recommended for patients with ≥ 4 axillary lymph node metastases, with a tumor size of ≥ 5 cm and in the presence of chest wall invasion, which may prevent local recurrence (8,12,14,16). Gefitinib and cetuximab, as therapeutic agents targeting EGFR/HER-1, are potent as novel treatment regimens (1,3,9,13,14).…”
mentioning
confidence: 99%